Assessment Of Scientific Reasoning-Communication Skills (Sr-Cs) Test on Work and Energy Concept: Development, Content Validity and Rasch Model Analysis - Fajar Fanika; Selly Feranie; Parlindungan Sinaga (Publikasi Indonesia, 2025)
Studies indicate that scientific reasoning assessments are still rarely integrated as higher-level assessments and new science education standards in school instruction. This study aims to develop a scientific reasoning skills test instrument that is integrated with a scientific communication skills test instrument (SR-CS test) on work and energy concept. This study used the ADDIE procedure. The research procedure consists of five stages including analyzing, designing, developing, implementing, and evaluating. The initial draft of SR-CS test consisted of 14 multiple choice scientific reasoning skills (SRS) questions and 8 open-ended scientific communication skills (SCS) questions. The results of the expert judgement were analyzed using the content validity index (CVI) and obtained a value of 0,94 (very suitable) for the SRS instrument and 0.97 (very suitable) for the SCS instrument. After being revised based on the expert suggestions, the test instrument was tested on 25 students (15 girls,10 boys) aged 16-17 years. The trial data were analyzed using the Rasch Model to obtained item fit (validity), reliability, distinction level, and difficulty level. The results show that 14 questions of SRS instrument have item validity and 8 questions of SCS instrument have item validity. Besides that, the item reliability of the SRS and SCS test instrument is 0.79 and 0.91, respectively. Meanwhile, the person reliability is 0.82 (SRS) and 0.91 (SCS). Therefore, the SR-CS test is valid and reliable so that it can be used to measure scientific reasoning skills and scientific communication skills of students in further research.